The Influence of Principal's Authentic Leadership, Responsible Management Education and Teacher Performance Motivation on Continuing Education in Public Junior High Schools in Jambi City - Zul Bahri; Mohamad Muspawi; Muhammad Sofwan (Universitas Muhammadiyah Enrekang, 2025)
Leadership plays a strategic role in realizing quality education. This study aims to analyze the influence of authentic leadership of principals, responsible management education, and teacher performance motivation on continuing education in junior high schools in Jambi City. This study uses a quantitative approach with a survey technique on principals and teachers. Data were obtained from 221 respondents and analyzed using Pearson correlation and multiple regression. The results of the analysis show that all three variables have a significant relationship with continuing education (p < 0.001), with responsible management education showing the highest correlation (r = 0.792). However, in the regression model, only responsible management education has a significant direct effect on continuing education (β = 0.762; p < 0.001). This model explains 62.9% of the variation in continuing education (R² = 0.629). These findings emphasize the importance of responsible management education practices in supporting the implementation of continuing education in schools. This study contributes to the development of educational leadership studies in Indonesia and recommends strengthening sustainability-based leadership training programs at the secondary education level.